Wheat rust research – Status, efforts and way ahead - Gupta, Neha; Batra, Neha; Bhardwaj, Subhash Chander (Journal of Cereal Research, 2014)
Wheat rusts caused by Puccinia species are the main biotic constraints in wheat production wherever wheat is grown. Their ability to spread aerially over the large distances, production of uredospores in enormous number and evolving new pathotypes, makes the management of wheat rusts a very daunting task. To overcome the threat of wheat rusts, efforts are going on worldwide for identification of pathotypes, anticipatory breeding, evaluation for rust resistance and deployment of rust resistant cultivars. Till now, more than 210 rust resistance genes and associated markers for many are available for the use of breeders. Some of the linked gene combinations like Lr34/Sr57/Pm38/Ltn1; Lr46/Yr29/Sr58/Pm39/Ltn2; Sr2/Yr30; Lr67/Yr46/Sr55/Ltn3 are known to confer durable resistance to different rusts. Efforts are on to introgress novel rust resistance from alien sources and revisiting rusts epidemiology. With the advent of genome sequences of wheat and wheat rusts, exploring the functional genomics and alternative approaches using next generation techniques are discussed in this review. Doi.org/ 10.25174/2249-4065/2017/60445